Terapi Slow Deep Breathing Terhadap Penurunan Nyeri Pada Pasien Dengan Cedera Kepala - Rusli Abdullah; Abdul Herman Syah Thalib; Siti Nurhalisa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction: Head injury is one of the cases that can cause death for the sufferer. Complaints that patients with head injuries often feel are headaches. One of the non-pharmacological techniques that can be done is slow deep breathing or slow deep breathing relaxation, which physiologically can cause a relaxing effect. Objective: Knowing the description of head-injured patients with Slow Deep Breathing therapy intervention in reducing Pain. Methods: a descriptive case study with the subjects used were two patients through inclusion and exclusion criteria. Results: respondent H experienced a decrease in pain level from a pain scale of 6 (moderate Pain) to a pain scale of 3 (mild Pain), and Respondent F experienced a decrease in pain level from a pain scale of 4 (moderate Pain) to a pain scale of 2 (mild Pain). Conclusion: Slow, Deep Breathing Therapy can reduce Pain.